Evaluation of potential health effects associated with occupational and environmental exposure to styrene – an update. (1st June 2019) - Banton, M.I.; Bus, J.S.; Collins, J.J.; Delzell, E.; Gelbke, H.-P.; Kester, J.E.; Moore, M.M.; Waites, R.; Sarang, S.S.
ABSTRACT: The potential chronic health risks of occupational and environmental exposure to styrene were evaluated to update health hazard and exposure information developed since the Harvard Center for Risk Analysis risk assessment for styrene was performed in 2002. The updated hazard assessment of styrene's health effects indicates human cancers and ototoxicity remain potential concerns. However, mechanistic research on mouse lung tumors demonstrates these tumors are mouse-specific and of low relevance to human cancer risk. The updated toxicity database supports toxicity reference levels of 20 ppm (equates to 400 mg urinary metabolites mandelic acid + phenylglyoxylic acid/g creatinine) for worker inhalation exposure and 3.7 ppm and 2.5 mg/kg bw/day, respectively, for general population inhalation and oral exposure. No cancer risk value estimates are proposed given the established lack of relevance of mouse lung tumors and inconsistent epidemiology evidence. The updated exposure assessment supports inhalation and ingestion routes as important. The updated risk assessment found estimated risks within acceptable ranges for all age groups of the general population and workers with occupational exposures in non-fiber-reinforced polymer composites industries and fiber-reinforced polymer composites (FRP) workers using closed-mold operations or open-mold operations with respiratory protection. Only FRP workers using open-mold operations not using respiratory protection have risk exceedances for styrene and should be considered for risk management measures. In addition, given the reported interaction of styrene exposure with noise, noise reduction to sustain levels below 85 dB(A) needs be in place.